2013
DOI: 10.1007/s10495-013-0813-y
|View full text |Cite
|
Sign up to set email alerts
|

TRIM16 overexpression induces apoptosis through activation of caspase-2 in cancer cells

Abstract: TRIM16 exhibits tumour suppressor functions by interacting with cytoplasmic vimentin and nuclear E2F1 proteins in neuroblastoma and squamous cell carcinoma cells, reducing cell migration and replication. Reduced TRIM16 expression in a range of human primary malignant tissues correlates with increased malignant potential. TRIM16 also induces apoptosis in breast and lung cancer cells, by unknown mechanisms. Here we show that overexpression of TRIM16 induces apoptosis in human breast cancer (MCF7) and neuroblasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 36 publications
1
20
0
2
Order By: Relevance
“…Another estrogen-responsive protein, TRIM16, which inhibits hepatocellular carcinoma cell migration and invasion by suppression of ZEB2 expression as well as suppresses cancer cell viability by involving interaction and stabilization of TDP43 with consequent eff ects on E2F1 and pRb proteins (Kim et al 2016), is also up-regulated in glioma cells without IRE1 signaling enzyme function. Moreover, TRIM16 inhibits neuroblastoma cells proliferation through cell cycle regulation and induces apoptosis via activation of caspase-2 (Bell et al 2013;Kim et al 2013). Th erefore, our results conform to data that FAM162A, PGRMC2, TRIM16, and SLC39A6 have mainly anti-proliferative functions through interaction with diff erent transcription coregulators and signaling pathways of ER stress in cell specifi c manner.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Another estrogen-responsive protein, TRIM16, which inhibits hepatocellular carcinoma cell migration and invasion by suppression of ZEB2 expression as well as suppresses cancer cell viability by involving interaction and stabilization of TDP43 with consequent eff ects on E2F1 and pRb proteins (Kim et al 2016), is also up-regulated in glioma cells without IRE1 signaling enzyme function. Moreover, TRIM16 inhibits neuroblastoma cells proliferation through cell cycle regulation and induces apoptosis via activation of caspase-2 (Bell et al 2013;Kim et al 2013). Th erefore, our results conform to data that FAM162A, PGRMC2, TRIM16, and SLC39A6 have mainly anti-proliferative functions through interaction with diff erent transcription coregulators and signaling pathways of ER stress in cell specifi c manner.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, recently was shown that TRIM16 inhibits cancer cell viability by a novel mechanism involving interaction and stabilization of TDP43 with consequent eff ects on E2F1 and pRb proteins (Kim et al 2016). Th ere is also data that TRIM16 inhibits neuroblastoma cells proliferation through cell cycle regulation and melanoma cells proliferation and migration through regulation of interferon beta 1 as well as induces apoptosis through activation of caspase-2 in cancer cells (Bell et al 2013;Kim et al 2013;Sutton et al 2014).…”
mentioning
confidence: 99%
“…TRIM16, also known as estrogen-responsive B-box protein (EBBP), is a member of the TRIM family and the functions are not yet fully elucidated (12). TRIM16 is a positive transcriptional regulator of the retinoic acid receptor β2 (13).…”
Section: Introductionmentioning
confidence: 99%
“…TRIM16 is a positive transcriptional regulator of the retinoic acid receptor β2 (13). It plays an important role in many different types of cancers, including neuroblastoma, non-small cell lung cancer (NSCLC) and melanoma (12). Overexpression of TRIM16 reduced neuroblastoma cell growth, enhanced retinoid-induced differentiation and decreased tumorigenicity in vivo (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Given the connections to autophagic machinery via TRIM16, the role of Galectin-3 in control of bacteria or pathology associated with mycobacterial infection can now be mechanistically linked to the TRIM-driven process of precision autophagy (Kimura et al, 2016), which differs from bulk autophagy. TRIM16 is also known as estrogen-responsive B box protein, and its role in cancer (a general property of TRIMs (Hatakeyama, 2011)) has been linked to specific effects on immune signaling (Sutton et al, 2014), cell survival (Kim et al, 2013), cell migration and metastasis (Marshall et al, 2010; Sutton et al, 2014) through various mechanisms, including measures of membrane repair (Cheung et al, 2012; Marshall et al, 2010), with the latter potentially overlapping with the processes described in this work.…”
Section: Discussionmentioning
confidence: 86%